2021
DOI: 10.3390/ijms23010161
|View full text |Cite
|
Sign up to set email alerts
|

Transient Focal Cerebral Ischemia Leads to miRNA Alterations in Different Brain Regions, Blood Serum, Liver, and Spleen

Abstract: Ischemic stroke is characterized by an occlusion of a cerebral blood vessel resulting in neuronal cell death due to nutritional and oxygen deficiency. Additionally, post-ischemic cell death is augmented after reperfusion. These events are paralleled by dysregulated miRNA expression profiles in the peri-infarct area. Understanding the underlying molecular mechanism in the peri-infarct region is crucial for developing promising therapeutics. Utilizing a tMCAo (transient Middle Cerebral Artery occlusion) model in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 101 publications
(116 reference statements)
0
2
0
Order By: Relevance
“…57 Here, serum levels of miR-181c were lower in streptozotocin-treated rats than in control rats, with no significant alteration observed when rats in the STZ+ICSS group were compared with control rats. Considering the studies that have shown associations between serum and tissue miRNA levels 58,59 and based on our previous findings showing upregulation of hippocampal miR-181c levels by MFB-ICSS in healthy rats, 9 we hypothesize that MFB-ICSS can reverse the memory and learning deficits in streptozotocintreated rats by modulating levels of hippocampal miR-181c. To examine this hypothesis, further research should aim to induce inhibition of miR-181c in the hippocampus of rats with AD-like pathology and analyze the effects of MFB-ICSS on behaviour and on the expression of its putative targets.…”
Section: Discussionmentioning
confidence: 89%
“…57 Here, serum levels of miR-181c were lower in streptozotocin-treated rats than in control rats, with no significant alteration observed when rats in the STZ+ICSS group were compared with control rats. Considering the studies that have shown associations between serum and tissue miRNA levels 58,59 and based on our previous findings showing upregulation of hippocampal miR-181c levels by MFB-ICSS in healthy rats, 9 we hypothesize that MFB-ICSS can reverse the memory and learning deficits in streptozotocintreated rats by modulating levels of hippocampal miR-181c. To examine this hypothesis, further research should aim to induce inhibition of miR-181c in the hippocampus of rats with AD-like pathology and analyze the effects of MFB-ICSS on behaviour and on the expression of its putative targets.…”
Section: Discussionmentioning
confidence: 89%
“…For IS, miRNA profiles are provided in the blood of patients [114,115] and in brain tissues [116]. MiRNA profiles were also obtained for rats after tMCAO in the blood and in various tissues, including different areas of the brain [117]. Profiles are also available for oxygen glucose deprivation/re-oxygenation (ODG/R)-induced cell cultures, including astrocytes [118].…”
Section: Micrornas In Is and Admentioning
confidence: 99%
“…One model may show the compensation state of some pathological process, while another will show the decompensation state. As an example, even in one animal model we have significant spatial [117] and temporal [156] transcriptomic changes.…”
Section: Micrornas In Is and Admentioning
confidence: 99%
“…Early studies have focused on the role of non-coding RNAs by showing that targeting specific microRNAs could potentially be a new avenue for developing effective stroke therapies [ 6 , 7 ]. Voelz et al, 2022 [ 8 ], studied the changes in miRNA expression in various tissues after an episode of transient focal cerebral ischemia (TFCI). The authors analyzed the miRNA expression in different brain regions, blood serum, liver, and spleen of rats that underwent TFCI and compared it to a control group.…”
mentioning
confidence: 99%